DISTRIBUTION OF Handroanthus heptaphyllus IN BRAZIL AND FUTURE PROJECTIONS ACCORDING TO GLOBAL CLIMATE CHANGE - Scarante, Andressa Godinho; Matos, Maria de F. da S.; Soares, Márcia T. S.; Aguiar, Ananda V. de; Wrege, Marcos S. (Revista Geama, 2017)
In this work, we mapped the distribution of Handroanthus heptaphyllus in Brazil and projected future scenarios of climate change, using potential distribution modeling (MDP). In the first step, we mapped the climate of the current period and for future scenarios (1961-1990, 2011-2041, 2041-2070 and 2071-2100, respectively). the next step, these maps were compared to the 114 points of occurrences of the species. The climate projections were made in accordance with scenarios presented in the 4th Assessment Report of the Intergovernmental Panel on Climate Change - AR4 / IPCC. The projections for the next decades indicate alterations in the distribution of H. heptaphyllus. Additionally, it demonstrated a significant reduction of distribution areas in the northern limit, with retreated ecological niche from latitudes south and to higher altitudes. We conclude that the preservation of H. ffThereby, protecting it from the climatic changes that will occur in the next decades. The BAGs with the populations this species should be established based on the same criteria for the seed collection areas, in order to maintain the similar environmental conditions and avoid the effects of undue external influences.